Fishing unfunctionalized SERS tags with DNA hydrogel network generated by ligation-rolling circle amplification for simple and ultrasensitive detection of kanamycin - Chen, Qian; Tian, Run; Liu, Gang; Wen, Yanli; Bian, Xiaojun; Luan, Donglei; Wang, Huiyuan; Lai, Keqiang; Yan, Juan (Biosensors & bioelectronics, 2022)
Simple assay format-based SERS methods for sensitive target substance analysis is of great significance for the development of on-site monitoring biosensors. Herein, taking the typical antibacterial kanamycin (KANA) as a subject, a simple, highly sensitive and specific SERS aptasensor was developed by manipulating DNA hydrogel network to fish plasmonic core-shell nanoparticles. A competitive binding mode of aptamer, ligation-rolling circle amplification (L-RCA), gap-containing Au@Au nanoparticles (GCNPs) with embedded Raman reporters were integrated into the sensor. In the presence of KANA, the double stranded DNA (dsDNA) structure of the aptamer was disrupted, and the released primers were used to construct two kinds of circularized padlock probes (CPPs) which were partially complementary. DNA hydrogel network was formed through the intertwining and self-assembly of two RCA-generated single stranded DNA (ssDNA) chains, during which GCNPs and magnetic beads (MBs) were entangled and incorporated. Finally, KANA quantification was successfully achieved through the quantification of the DNA hydrogel. Overall, this novel SERS aptasensor realized a simple and ultrasensitive quantification of KANA down to 2.3 fM, plus excellent selectivity, and precision even for real food samples. In view of innovative fusion across L-RCA-based DNA hydrogel and SERS technique, the proposed method has promising potential for application in on-site detection and quantification of trace food contaminants. [Display omitted]